Evaluating the feasibility of complex interventions in mental health services: standardised measure and reporting guidelines - Bird, Victoria; Le Boutillier, Clair; Leamy, Mary; Williams, Julie; Bradstreet, Simon; Slade, Mike (Royal College of Psychiatrists, 2014)
Aims: To develop a) an empirically-based standardised measure of the feasibility of complex interventions for use within mental health services and b) reporting guidelines to facilitate feasibility assessment. Method: A focussed narrative review of studies assessing implementation blocks and enablers was conducted with thematic analysis and vote counting used to determine candidate items for the measure. Twenty purposively sampled studies (15 trial reports, 5 protocols) were included in the psychometric evaluation, spanning different interventions types. Cohen’s Kappa was calculated for inter-rater reliability and test-retest reliability. Results: 95 influences on implementation were identified from 299 reviewed references. The final measure - Structured Assessment of Feasibility (SAFE) - comprises 16 items rated on a Likert scale. SAFE demonstrated excellent inter-rater (kappa 0.84, 95% CI 0.79 - 0.89) and test re-test reliability (kappa 0.89, 95% CI 0.85 - 0.93). Cost information and training time were the two influences least likely to be reported in intervention papers. SAFE Reporting Guidelines include 16 items organised into 3 categories (Intervention, Resource consequences, Evaluation). Conclusion: SAFE is a novel approach to evaluating interventions, and supplements efficacy and health economic evidence. SAFE Reporting Guidelines will allow feasibility of an intervention to be systematically assessed.